Response Of Papaya (Carica papaya L.) Seeds Growth To The Gibberellin (GA3) and Cow Biourine - Jhon Hardy Purba; Nyoman Srilaba; Putu Sri Wahyuni; Putu Bayu Wahyuda (JURNAL AGRONOMI TANAMAN TROPIKA (JUATIKA), 2021)
Papaya propagation from seeds has a major problem, namely seed germination takes a relatively long time. Experiments to determine the effect of gibberellin and cow bio urine concentrations on the growth of papaya seedlings were carried out at the Main Horticultural Seed Center of the Agriculture and Livestock Service Office of Buleleng Regency with an altitude of ± 200 m above sea level. The experiment used a factorial randomized block design consisting of two factors, namely the concentration of gibberellin and the concentration of bovine bio urine. Application of gibberellin significantly affected plant height, root length, root wet weight, root oven-dry weight, leaf wet weight, leaf oven-dry weight, total fresh weight, and total oven-dry weight. Gibberellin with a concentration of 150 ppm gave the highest total fresh weight and oven-dry weight, namely 14.63 g and 1.44 g respectively compared to other treatments. The concentration of cow bio urine had a significant effect on root length, very significantly on plant height 40 DST and 47 dd, stem oven-dry weight, leaf wet weight, leaf oven-dry weight, total fresh weight, and total oven-dry weight. Biourine with a concentration of 200 ml.l-1 gave the highest yield in total oven-dry weight per plant, namely 1.19 g. The combination of the concentration of gibberellin and bovine bio urine significantly affected the root length of the plant.